Liquid Chromatography–Mass Spectrometry Study Focusing on Neuroprotective Effect of Compounds Obtained from Bacopa monnieri Juice (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: According to Ayurvedic literature, Brahmi is highly recommended for the management ofpsychiatric problems since it acts on the brain. In traditional Ayurvedic medicine, Brahmi, a herb is recommendedfor the management of various psychological disorders such as Alakshmi (inauspicious condition), Unmada(insanity), and Apasmara (epilepsy). Drug quality is a basic necessity in this day and age, and analytical testingcan help combat impurities or subpar pharmaceuticals. Materials and Methods: Compound analysis of BrahmiJuice ( Swarasa) using liquid chromatographic mass spectrometry (LC-MS). Results: LC-MS analysis showsmajor compound such as L-Phenylalanine, Phenylacetylene, DL-Arginine, Azelaic acid, Erucamide, D-(+)-Pyroglutamic acid, L-Glutamic acid, Valine, Choline, L-Isoleucine, DL-Tryptophan, L-(-)-Methionine, andBeta-Ionone which play a significant role in neuroprotection. Conclusion: The study showed the presence ofcompounds rich in neurotransmitters which also act as neurotonics having their specific neuroprotective effectin conditions such as Alzheimer’s Disease, Parkinsonism, and Dementia. By employing a wide array of testingprocedures, manufacturers are able to ensure compliance with regulatory requirements and supply consumers witha better product that effectively delivers Brahmi’s therapeutic benefits.